Eco-Awareness and Marketing Strategy of Generation Z: A Bibliometric Study - Judijanto, Loso; Hasan, Hanif; Ardhiyansyah, Andri (Westscience Press, 2025)
This study presents a bibliometric analysis of the academic literature at the intersection of eco-awareness and marketing strategies with a specific focus on Generation Z. Using data retrieved from the Scopus database and analyzed through VOSviewer, the study maps keyword co-occurrence patterns, author collaboration networks, temporal research trends, and country-level contributions. The findings reveal that research in this field is centered on core themes such as sustainability, green marketing, and consumer behavior, with increasing attention to emerging topics like sustainable consumption, eco-labeling, and environmental attitudes. Prominent contributors include authors from India, China, and the United States, while collaboration networks indicate strong intra-regional ties but limited cross-regional integration. The study identifies significant research gaps in underrepresented regions and calls for deeper interdisciplinary and intercultural engagement. The results provide valuable insights for academics and practitioners seeking to understand and engage the eco-conscious behavior of Generation Z through effective and authentic marketing strategies.